1992
DOI: 10.1148/radiology.185.2.1410369
|View full text |Cite
|
Sign up to set email alerts
|

Human focal cerebral ischemia: evaluation of brain pH and energy metabolism with P-31 NMR spectroscopy.

Abstract: The authors investigated early human focal ischemia with phosphorus-31 nuclear magnetic resonance spectroscopy at 1.89 T to characterize the temporal evolution and relationship of brain pH and phosphate energy metabolism. Data from 65 symptomatic patients were prospectively studied; none of the patients had had ischemic stroke in the internal carotid artery territory before. Twenty-eight neurologically normal individuals served as control subjects. Serial ischemic brain pH levels indicated a progression from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 0 publications
6
43
0
2
Order By: Relevance
“…After the procedure described by Levine et al, 3 the frequency area for signals from inorganic phosphate at 3.6 to 5.6 ppm relative to phosphocreatine at 0 ppm was analyzed by a single Lorentzian line with variable line width, frequency, and intensity (single-peak approach). The position of this peak was used to establish a general pH value.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…After the procedure described by Levine et al, 3 the frequency area for signals from inorganic phosphate at 3.6 to 5.6 ppm relative to phosphocreatine at 0 ppm was analyzed by a single Lorentzian line with variable line width, frequency, and intensity (single-peak approach). The position of this peak was used to establish a general pH value.…”
Section: Data Processingmentioning
confidence: 99%
“…1,2 However, a reversal from acute acidosis to subacute alkalosis has been described in longitudinal studies using MRS. 3,4 Acute ischemia is expected to show a near complete depletion of energy substrates in the center of the infarct as reflected in drastically reduced levels of phosphocreatine, ATP, and increased levels of inorganic phosphate (Pi).1 Phosphocreatine is an important energy source to regenerate ATP from ADP by creatine kinase reaction. Owing to the breakdown of energy metabolism, the vast majority of total creatine (tCr) should, therefore, be unphosphorylated creatine (uCr).…”
mentioning
confidence: 99%
“…Of particular interest, phosphorous-31 ( 31 P) MRS and MRI allow the evaluation of several important aspects of high-energy phosphate metabolism, from metabolite concentrations to metabolic fluxes through ATP-generating enzymes. Since 1970s, numerous studies have employed 31 P-MRS/MRI in the investigation of a broad range of diseases such as diabetes, stroke, heart failure, and cancers (3)(4)(5)(6)(7)(8). These studies have provided invaluable insights into the role of mitochondrial metabolism in normal physiology and disease development.…”
Section: Introductionmentioning
confidence: 99%
“…Adult clinical studies have demonstrated brain intracellular alkalosis in areas of chronic infarction after stroke (15,16) with a significant correlation between brain alkalosis and subsequent poor clinical outcome (17). We have recently observed a similar relationship between brain intracellular alkalosis and the severity of brain injury in term infants with NE (18).…”
mentioning
confidence: 99%